Association of ABCB4 and ABCB11 nucleotide variants with intrahepatic cholestasis of pregnancy - Gruszczyńska-Losy, Milena; Mostowska, Adrianna; Adamczak, Łukasz; Jagodziński, Paweł; Wender-Ożegowska, Ewa; Kędzia, Małgorzata (Journal of Medical Science, 2019)
Background. Intrahepatic cholestasis of pregnancy (ICP) is the most common liver disorder during gestation. The exact pathogenesis of ICP is multifactorial and still unclear. Therefore, our study aimed to check whether the selected ABCB4and ABCB11nucleotide variants are associated with an increased risk of ICP.Methods. ICP was diagnosed based on clinical symptoms characteristic of this disease and confirmed by increase in serum bile acids and transaminases, spontaneous resolution of clinical symptoms and normalization of laboratory tests after delivery. The total of 86 pregnant women meeting the criteria were included into the study. Healthy pregnant women with uncomplicated pregnancy served as control group (n=310). Sixcommon nucleotide variants in theABCB11and ABCB4genes were genotypedwith the use of high-resolution melting curve analysis.Conclusions. Our study did not show any significant association of analysed ABCB4and ABCB11nucleotide variants with the increased risk of intrahepatic cholestasis of pregnancy.
Keywords: Intrahepatic Cholestasis of Pregnancy; ABCB4; ABCB11; nucleotide variants